THE FUNCTION AND POSITION OF PENGHULU IN RAFFLES’ KITAB HUKUM MANUSCRIPT (1814) (JOURNAL OF INDONESIAN ISLAM, 2019)
In this article, we discuss the function and position of penghulu in Java in the second decade of the nineteenth century. The object of this study is a manuscript from the British Library collection, coded Mss Eur D/742.1, ff. 155-166, that was issued by Thomas Stamford Raffles, the Lieutenant-Governor of Java, and Its Dependencies, on 11 February 1814. The manuscript actually regulates the general justice system. However, in this article, we will only discuss a number of rules that are directly related to the function and position of penghulu in the justice system. The paper will show that penghulu, in Raffles’ regulation, was functioned as an expert to be presented to a court. He must expound about Islamic law or customary law related to cases that were being handled by the court. In fact, when it was first formed in the early days of the Demak Sultanate (1475-1554), the penghulu was a representative of the sultan and is held responsible for the implementation of the rules of Islam. Meanwhile, in the field of law, the penghulu was head of the court.